Evolution of mantle melts and fluids at the Precambrian - Usenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the example of magmatic complexes of the Ukrainian Shield, it is shown that the composition of the Archean-Paleoproterozoic deep mantle fluids changed regularly. Oxidized and acidic fluids, specific to the Archean, were replaced in the Paleoproterozoic by neutral aqueous potassium chloride ones and, after 2.0 billion years, by alkaline carbonate-sodium fluoride ones. This determined the evolution of igneous rocks of the Precambrian.